The Relationship between Economic Growth and International Trade - Olima, Khudoyberdiyeva (Journal of Innovation in Education and Social Research, 2025)
This article explores the dynamic relationship between economic growth and international trade, emphasizing how cross-border exchange of goods and services serves as a key engine of national development. Drawing from classical economic theories and modern empirical evidence, the paper highlights how trade contributes to growth by enabling access to larger markets, encouraging specialization, promoting technology transfer, and enhancing productivity through competition. Case studies of rapidly developing economies—such as China and the East Asian Tigers—demonstrate how strategic integration into global markets has catalyzed sustained growth. However, the analysis also acknowledges the limitations of trade-led growth, including rising inequality, trade imbalances, and vulnerability to external shocks. In light of recent disruptions such as the COVID-19 pandemic and geopolitical tensions, the article concludes by advocating for more resilient and inclusive trade policies that align economic expansion with social and environmental goals.